A study of the informal interactions between audit committees and internal auditors in Australia - Sarens, Gerrit; Christopher, Joseph; Zaman, Mahbub (Wiley-Blackwell Publishing Asia, 2013)
This paper finds evidence for the growing importance of informal interactions between the internal audit function and the audit committee (AC) in Australia – a relatively unexplored topic in the literature – using a survey of Chief Audit Executives (CAEs). It also describes the nature of these informal interactions. The most innovative elements of this paper are the findings that certain personal characteristics of CAEs, the specific knowledge and expertise of the AC chair, as well as some of the AC chair’s personal characteristics are associated with the existence (and increase) of informal interactions.